A Study on Rainfall Rate, Temperature and Rain Attenuation of Ka-Band Satellite signal: https://doi.org/10.69692/SUJMRD1004121 - XAYAPHONE, Soyfa; LAKANCHANH, Donekeo (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research paper is studied rainfall, temperature and rain attenuation of Ka-Band satellite signal by using rainfall and temperature data in 2023. Department of Electronics and Telecommunications Engineering, Faculty of Engineering is where the station is housed. Therefore, this paper aims to investigate the relationship between rainfall values, temperature and rain attenuation in Vientiane Capital using advanced technologies to facilitate and monitor the data in real time. A rain gauge Tipping Bucket 0.1mm/Tip is used to detect the amount of rain, and a DHT22 sensor is used to monitor the temperature. The research procedure entails analyzing temperature and rainfall, designing and setting up measurement sites, setting up a central monitoring station and using the Internet of Things to collect temperature and rainfall data. The analysis showed that the high precipitation amount of the actual rainfall and actual daily data contains two maximum values from August 15, 2023 at 85.3mm/hr with 26°C and September 7, 2023 at 110mm/hr with 25.1°C. ITU-R model is used to analyze the rain attenuation by applying the abovementioned rainfall values. As a result, the rain attenuation of Ka-Band Satellite Signal is 85.3mm/hr the rain attenuation is 11.63 dB and 110mm/hr the rain attenuation is 10.58 dB, respectively, which showed the interlinkage between rainfall amount and temperature while it is raining. The temperature change will not affect the rain attenuation as much as the increase of rainfall amount.